PENGARUH UNSUR-UNSUR KEPUASAN PENGGUNA PADA EFISIENSI DAN EFEKTIVITAS KERJA PENGGUNA APLIKASI SISTEM AKUNTANSI INSTANSI DI SATUAN KERJA PENDIDIKAN TINGGI DI PROVINSI BALI - Perdanawati, Virra Indah; Rasmini, Ni Ketut; Wirama, Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03.NO.08.TAHUN 2014, 2014)
1024x768 ABSTRACT The aim of this research is to evaluate the effect of user sastisfaction on work efficiency and effectiveness of the users of accounting system application at higher education institution in the Province of Bali. User satisfaction is measured by function completeness, stability, simple of use, innovation, safety, and flexibility. The research uses 45 respondents who are accounting system operators in 7 higher education officer in the Province of Bali. Multiple regresion analysis showes that user satisfaction factors affect efficiency and effectiveness of accounting application systems. However, based on t test result, efficiency is affected by function completeness and flexibility only, while effectiveness is affected by safety variable only. Keywords: application system, user satisfaction, efficiency, effectiveness Normal 0 false false false EN-US X-NONE X-NONE
Keywords: application system, user satisfaction, efficiency, effectiveness